FIQIH BERSUCI DARI HADAS BESAR DAN HADAS KECIL - Okta Aidil Fitri; Ardila; Sandi Akib; Muhamad Afandi (JUTEQ: JURNAL TEOLOGI & TAFSIR, 2026)
Purification (thaharah) is one of the fundamental pillars of Islamic worship. No prayer is considered valid without first purifying oneself from both major and minor ritual impurities (hadas) and physical impurities (najis). This article comprehensively discusses the concept of purification from major and minor ritual impurities based on the Qur'an, Hadith, and the opinions of scholars from various Islamic schools of jurisprudence. The study covers the definition of thaharah, the classification of ritual impurities, the procedures of wudu (ablution), ghusl janabah (ritual bath), tayammum as an alternative means of purification, and the factors that invalidate purification. The method employed is library research using a normative-comparative approach among the schools of Islamic jurisprudence. The findings indicate that Islam provides systematic and comprehensive guidelines regarding purification, aiming to preserve both the physical and spiritual purity of Muslims.